Gasparee Island, Trinidad, B.W.I. - (:unkn) unknown (Y. De Lima and Co., 2011)
The postcard shows some of the small islands and the mainland of Trinidad from the island of Gasparee. It includes a handwritten note, is addressed to Mr. and Mrs. Kimble Winterton of New York, United States of America and postdated 17 February, 1939.
Colour: Sepia with hues of light blue; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Islands--Trinidad and Tobago; 1939; Gaspar Grande; Gasparee